Applicability of devices available for the measurement of intracompartmental pressures: a cadaver study - Sanne Vogels; Ewan D. Ritchie; Djuna deVries; Gert‐Jan Kleinrensink; Michiel H. J. Verhofstad; Rigo Hoencamp (Journal of Experimental Orthopaedics, 2022)
Abstract Purpose The indication for surgical treatment of the chronic exertional compartment syndrome is evaluated by measuring intracompartmental pressures. The validity of these invasive intracompartmental pressure measurements are increasingly questioned in the absence of a standardized test protocol and uniform cut‐off values. The aim of the current study was to test compartment pressure monitors and needles for uniformity, thereby supporting the physician’s choice in the selection of appropriate test materials. Methods A compartment syndrome was simulated in embalmed above‐knee cadaveric leg specimen. Four different terminal devices (Compass manometer, Stryker device, Meritrans transduce, and arterial line) were tested with 22 different needle types. Legs were pressurized after introduction of the four terminal devices in the anterior compartment, using the same needle type. Pressure was recorded at a 30‐second interval for 11 minutes in total. Before and after pressurization, the intravenous bag of saline was weighed. Results The simulation of a compartment syndrome resulted in intracompartmental pressure values exceeding 100 mmHg in 17 of the 22 legs (77%). In the other five legs, a smaller built‐up of pressure was seen, although maximum intracompartmental pressure was in between 70 and 100 mmHg. The intraclass correlation coefficient was above 0.700 for all possible needle types. Excellent to good resemblance was seen in 16 out of 22 instrumental setups (73%). The mean volume of saline infusion required in runs that exceeded 100 mmHg (309 ± 116 ml) was significantly lower compared to the legs in which 100 mmHg was not achieved (451 ± 148 ml; p = 0.04). Conclusion The intracompartmental pressure recordings of the four terminal devices were comparable, when tested with a standardized pressurization model in a human cadaver model. None of the included terminal devices or needle types were found to be superior. The results provide evidence for more diverse material selection when logistic choices for intracompartmental pressure measurement devices are warranted. Level of evidence Level IV.